Message from the Chief Editor: JTET December 2018 - Editor, Chief (Journal of Technical Education and Training, 2018)
Welcome to the December 2018 issue of the Journal of Technical Education and Training. In this issue, eight papers on TVET practices from Indonesia, Korea, Malaysia and Nigeria are shared, focussing on three main challenges in TVET namely, teacher preparations and performance, workers’ competence requirements and development, and teaching and learning approach. The first paper by Woo, Kim, Yi, and Yoon from Korea reports on how TVET trainers with and without certifications have contributed to Korean TVET training outcomes with discernible differences observed depending on the certification status – with or without. The second paper by Ismail, Nopiah and Rasul on the other hand discusses the challenges faced by novice TVET trainers in Malaysian public training institutions. Authors of both papers further make recommendations on how trainers’ competence can be further enhanced to fully meet each nation’s expectations. The third paper by Raymond, Uduafemhe, Alome, and Bamidele from Nigeria is looking at individual differences between trainers, and how these differences subsequently influences their teaching behaviours. Specifically the paper highlights the influences of TVET trainers’ personality traits towards their creative behaviour. Understanding gained from this information could very well be used in teacher recruitments and professional development. In the fourth and last paper on the issue of teacher preparation by Ismail, Hassan, Abu Bakar, Hussin, Mat Hanafiah and Asary, a proposal on a Malaysian TVET teacher training framework for ensuring TVET trainers’ competence to meet the Nation’s future labour needs is presented. The framework development has incorporated the unique nature and context of the Malaysian industry sector. The fifth to seventh paper present issues related to workers’ competency requirements and developments. The fifth paper by Marde Suarta establishes industry needs in Indonesia for new workers using advertisement analysis. The competence identified can be of relevance to Indonesia as well as other international agencies that may have dealings with labour force in the country. The sixth paper by Teguh Iman Santoso and Hassan discusses a proposal for an Indonesian TVET training framework. The framework may be of relevance to researchers who are looking at workforce trainings in Asia. In the seventh paper, Lilis Widaningsih, Mohammad Syaom Barliana, Tutin Aryanti, and Elly Malihah discuss a unique, rarely reported, alternative pathway to vocational skills acquisitions – the inheritance pathway. Their paper discusses how vocational skills are inherited through generation and networks of highly skilled family members. The inheritance training is an out-of-institution and sustainable approach to vocational skills development which should be of interest to those who are researching on the community of practice. In paper number eight, an innovative approach for supporting students’ problem solving skills development, the Conceive-Design-Implement-Operate (CDIO) approach is discussed by Jambari and colleagues from Malaysia. Despite the localised example, the approach can have global applications which readers may read in future issues of this journal. Last but not least, I would like to give a special mention of gratitude towards all our contributing authors, reviewers and editorial team for making the timely publication of this issue possible. Professor Dr. Maizam Alias Chief Editor